A clinical study of a family with Cockayne's syndrome. Issue 4 (August 1981) - Proops, Rosalyn; Taylor, A M R; Insley, J
Abstract : Two sibs with Cockayne's syndrome are described. The recognised cellular sensitivity to ultraviolet light is confirmed. The clinical features in the two children are described and comparisons are made with some forms of xeroderma pigmentosum, a condition in which there is progressive neurological degeneration and cellular sensitivity to ultraviolet irradiation.